Design and Fabrication of Polygonal Hole Machining Attachment - SHIVA KUMAR B, SIVA MANI N, LOGANATHAN M, SRI KUMAR D and LAL L N CHANDRA (1993)
INTERNAL GUIDE: VENKATARANGA REDDY D, MVJCE
Keywords: Polygonal Hole Machining Attachment